Promoting a culture of fairness: police training, procedural justice, and compliance - Sargeant, E. (Journal of experimental criminology, 2017)
Academics and practitioners alike are concerned about the potential “double-edged sword” of procedural justice. In the organizational context, procedural justice is expected to increase compliance with supervisors. However, blind, unthinking, or “hard” compliance with supervisors, may lead to anti-organizational behavior and misconduct. The present study examines the moderating effect of a police recruit cultural training program on the relationship between procedural justice and compliance with police supervisors. We expect that providing cultural training will moderate the relationship between procedural justice and “hard” compliance.